1997
DOI: 10.1021/ie9604177
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Branched Glycidyl Azide Polymer Purified by Solvent Extraction

Abstract: Dimethyl sulfoxide (DMSO), a polar liquid of low volatility, was used as solvent in the synthesis of branched glycidyl azide polymer (GAP) which is a potential energetic binder for rocket propellants. Branched GAP product was purified by an extraction method using dichloromethane to create an organic phase and a mixture of methanol−brine (50:50 in weight) as the extracting solution. The extraction was carried out in four steps, leaving only less than 1% DMSO in the purified branched GAP. The DMSO concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Chung et al discussed the effect of Lewis acid on the mechanical properties of PUs. Bui et al reported that the presence of low-volatile solvent such as dimethyl sulfoxide in the polymerization reaction mixture increases the tensile properties of the PUs. In our latest report, , we observed that the functionalized HTPB at the terminal carbon with nitrogen-rich molecules significantly improved the tensile property due to the presence of strong hydrogen bonding and electrostatic interactions in the PUs chain.…”
Section: Introductionmentioning
confidence: 99%
“…Chung et al discussed the effect of Lewis acid on the mechanical properties of PUs. Bui et al reported that the presence of low-volatile solvent such as dimethyl sulfoxide in the polymerization reaction mixture increases the tensile properties of the PUs. In our latest report, , we observed that the functionalized HTPB at the terminal carbon with nitrogen-rich molecules significantly improved the tensile property due to the presence of strong hydrogen bonding and electrostatic interactions in the PUs chain.…”
Section: Introductionmentioning
confidence: 99%
“…Although GAPs were first reported in the 1970s, work on GAPs is an ongoing effort worldwide, especially in the area of synthesizing new structural GAPs. GAPs with various topological structures have been designed and prepared (branched GAPs, star‐type GAP oligomers, diblock or triblock copolymers of GAPs, grafting compounds of GAPs, etc.) in order to overcome some problems of general linear GAPs in application, such as low molecular weight (2000–5000 g mol −1 ), short polyether main chain, poor low‐temperature properties and so on .…”
Section: Introductionmentioning
confidence: 99%
“…Lewis acid treatment of lignin enhances the concentration and reactivity of hydroxyl groups available to react with diisocyanate monomers which results in better integration of lignin into the urethane network; hence, the mechanical properties improve significantly . PUs obtained from glycidyl azide polymer (GAP), an alternative energetic binder to HTPB for rocket propellants, displayed tunable tensile properties depending upon the amount of residual dimethyl sulfoxide solvent which was used to synthesize the GAP prepolymer . Zhang et al reported simultaneous improvement of tensile strength, Young’s modulus, and elongation at break in the case of a polyurethane hybrid obtained from functionalized modified hexamethylene diisocynate trimer and dihydroxyl propyl-terminated siloxane oligomers .…”
Section: Introductionmentioning
confidence: 99%